2018
DOI: 10.1161/strokeaha.118.022128
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous tPA (Tissue-Type Plasminogen Activator) in Patients With Acute Ischemic Stroke Taking Non–Vitamin K Antagonist Oral Anticoagulants Preceding Stroke

Abstract: Background and Purpose— Although there are no trials or large cohorts to inform clinical care, current guidelines caution against giving intravenous tPA (tissue-type plasminogen activator) to patients with acute ischemic stroke who are taking non–vitamin K antagonist oral anticoagulants (NOACs). We performed a literature review of intravenous tPA in patients treated with NOACs preceding stroke. Methods— A literature search of PubMed was performed encomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Seiffge et al estimated that IVT could be used in more than half of patients with prior rivaroxaban treatment with about 28% of patients denied by current guidelines [30,45,81]. Recent analyses concluded that IVT is probably effective and safe in select AIS patients undergoing NOAC treatment [8184]. However, optimal patient selection is dependent on coagulation parameters that have not yet been sufficiently evaluated, and the variable selection criteria used in available studies do not allow for a consensus [39,42,85,86].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seiffge et al estimated that IVT could be used in more than half of patients with prior rivaroxaban treatment with about 28% of patients denied by current guidelines [30,45,81]. Recent analyses concluded that IVT is probably effective and safe in select AIS patients undergoing NOAC treatment [8184]. However, optimal patient selection is dependent on coagulation parameters that have not yet been sufficiently evaluated, and the variable selection criteria used in available studies do not allow for a consensus [39,42,85,86].…”
Section: Discussionmentioning
confidence: 99%
“…Initial reports on successful and safe IVT after idarucizumab administration are promising, but limited experience does not allow for a final statement on the safety of IVT after antagonization [33,84]. Additionally, it is not clear whether idarucizumab/IVT should be administered in every dabigatran patient with an AIS or only if direct EVT is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Even if limited on anecdotal experiences of case reports and series this review provides further evidence that patients taking NOACs in general might not have an increased bleeding risk upon intravenous thrombolysis. With respect to dabigatran only, authors found, that patients treated with idarucizumab were significantly more likely to have favorable outcomes and are numerically less likely to bleed and die ( 19 ). The here presented case is another one without hemorrhagic complication.…”
Section: Discussionmentioning
confidence: 99%
“… 63 Similarly, a literature review documented rates of sICH following IVT of 4.3% in selected AIS patients pre-treated with NOACs, despite a median time interval from the last dose of the anticoagulant to IVT of only 8 h. Moreover, the administration of idarucizumab before IVT in 44 dabigatran pre-treated patients resulted in numerically fewer sICHs (4.5% versus 7.4%) and deaths (4.5% versus 12.0%). 64 Although both reviews conclude that in selected patients with NOAC pre-treatment IVT may not increase sICH, more data are needed to clarify the safety of IVT in this group of patients, particularly when specific coagulation assays to assess residual anticoagulant activity at patient presentation are not available.…”
Section: Anticoagulation Pre-treatmentmentioning
confidence: 99%